2020
DOI: 10.1111/dth.14312
|View full text |Cite
|
Sign up to set email alerts
|

Management of pernio‐like cutaneous manifestations in children during the outbreak of COVID‐19

Abstract: Background During the outbreak of COVID‐19 many pernio‐like lesions have been increasingly reported. The aim of the study is to describe our management of these skin manifestations and to evaluate a possible correlation to SARS‐CoV‐2 infection. Methods All patients underwent clinical and laboratory tests to detect a possible underlying connective disease and also to specific SARS‐CoV‐2 investigations such as oropharyngeal swab and IgG‐IgM serology. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 20 publications
(26 reference statements)
0
29
0
2
Order By: Relevance
“… [ 367 ] Chilblain-like lesions 4 M, 5 F 11 N.A. [ 368 ] Abbreviations: N.A. : information not available.…”
Section: Resultsmentioning
confidence: 99%
“… [ 367 ] Chilblain-like lesions 4 M, 5 F 11 N.A. [ 368 ] Abbreviations: N.A. : information not available.…”
Section: Resultsmentioning
confidence: 99%
“…Management of common chronic inflammatory skin diseases, as well as skin cancers or consequences of personal protective devices use were also discarded. Very few reports explicitly included as keywords or title the therapeutic approach for the occurrence of skin lesions associated with COVID-19 infection, 35 , 36 and several expert reviews were also considered to collect information on recommended treatment. 13 , 14 , 15 , 16…”
Section: Methodsmentioning
confidence: 99%
“…The majority of reports concerned chilblain/pernio-like cutaneous manifestations and specify that no treatment was needed. 28 , 36 , 39 , 40 , 41 , 42 For isolated cases, 37 , 38 two expert opinion leaders suggested that high-potency topical corticosteroids may be helpful if the lesions were causing discomfort. 16 , 43 …”
Section: Observationsmentioning
confidence: 99%
“…The Southwest Respiratory and Critical Care Chronicles 2021;9(39): [15][16][17][18][19][20][21] retrospective review of 26 children with COVID toes in Italy in March-April 2020 also demonstrated that all patients recovered without any treatment. 22 In these studies and other published case reports, a variety of treatments have been used. Patients have received symptomatic treatment (oral analgesia and antihistamines), topical heparin, topical nitroglycerin, and topical and systemic corticosteroids.…”
Section: Managementmentioning
confidence: 99%
“…Patients have received symptomatic treatment (oral analgesia and antihistamines), topical heparin, topical nitroglycerin, and topical and systemic corticosteroids. [21][22][23][24] To date, no randomized control trials have been performed to assess the efficacy of treatment for COVID toes.…”
Section: Managementmentioning
confidence: 99%